Microarray analysis of human keratinocytes from different anatomic sites reveals site-specific immune signaling and responses to human papillomavirus type 16 transfection - Mohd Israr; David Rosenthal; Lidia Frejo-Navarro; James DeVoti; Craig Meyers; Vincent R. Bonagura (BMC, 2018)
Abstract Background Stratified human keratinocytes (SHKs) are an essential part of mucosal innate immune response that modulates adaptive immunity to microbes encountered in the environment. The importance of these SHKs in mucosal integrity and development has been well characterized, however their regulatory immunologic role at different mucosal sites, has not. In this study we compared the immune gene expression of SHKs from five different anatomical sites before and after HPV16 transfection using microarray analyses. Methods Individual pools of human keratinocytes from foreskin, cervix, vagina, gingiva, and tonsils (HFKs, HCKs, HVKs, HGKs and HTLKs) were prepared. Organotypic (raft) cultures were established for both normal and HPV16 immortalized HFKs, HCKs, HVKs, HGKs and HTLKs lines which stably maintained episomal HPV16 DNA. Microarray analysis was carried out using the HumanHT-12 V4 gene chip (Illumina). Immune gene expression profiles were obtained by global gene chip (GeneSifter) and Ingenuity pathway analysis (IPA) for each individual site, with or without HPV16 transfection. Results We examined site specific innate immune response gene expression in SHKs from all five different anatomical sites before and after HPV16 transfection. We observed marked differences in SHK immune gene repertoires within and between mucosal tracts before HPV 16 infection. In addition, we observed additional changes in SHKs immune gene repertoire patterns when these SHKs were productively transfected with HPV16. Some immune response genes were similarly expressed by SHKs from different sites. However, there was also variable expression of non-immune response genes, such as keratin genes, by the different SHKs. Conclusions Our results suggest that keratinocytes from different anatomical sites are likely hard wired in their innate immune responses, and that these immune responses are unique depending on the anatomical site from which the SHKs were derived. These observations may help explain why select HPV types predominate at different mucosal sites, cause persistent infection at these sites, and on occasion, lead to HPV induced malignant and benign tumor development.